log b 1 = 0 c 0 = 1. When x 0 and/or b 0, the logarithm is undefined. Examples: log b 0 = undefined. log b ... (x + 5) (x + 2)] = log 2 (x + 6) (x + 5 ...
Read more

Positive: 45 %

Simple and best practice solution for log[5](x-7)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to ...
Read more

Simple and best practice solution for log[5](15x+5)-log[5](x)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and ...
Read more

Positive: 40 %

Solution for log^5(x-1)=2 equation: Simplifying log 5 (x + -1) = 2 Reorder the terms: g 5 lo(-1 + x) = 2 (-1 * g 5 lo + x * g 5 lo) = 2 (-1g 5 lo + g 5 lox ...
Read more

Positive: 26 %

Simple and best practice solution for 2+log(5)(x-2)=log(5)(15x) ... =-1 | | +46=-2+8n | | 6n+4=8n-7 | | -7(v-4)+3v+6=8v+8 | | 142=x(5+y) | | -x+8y=3 | | (x ...
Read more

Positive: 3 %

Show more results

Simple and best practice solution for log[5]x-log[5]2=log[5] ... (x+5)=6x-2 | | 159=7(5)+40 | | x^6-4x^5+4x^4-16x^2+64x-64=0 ... x^2-5*x+8=0 | | x^3+3x^2 ...
Read more

Positive: 45 %

Simple and best practice solution for log[5](x^2-16)-log[5](x-4)=log[5]17 equation. ... -7(n+3)-(9n-2)=-17n | | 4(x+5)+(x-6)= | | -4p20/3 | | 0.0725timesx ...
Read more

Positive: 44 %

(3x+7)(x-2)] =1 using log(a) + log(b) = log(ab) ... If y = log 5 ( log 5 x ) then dy/dx = 1] 1 x log 5 x 2] 1 x log 5 x.log 5x 3] 1 x log 5 x ...
Read more

Positive: 39 %

Simple and best practice solution for log[5](x-2)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to ...
Read more

Positive: 32 %

Simple and best practice solution for log[5](x^2-24x)=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to ...
Read more

Positive: 22 %

Simple and best practice solution for log[5](x)-2=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to ...
Read more

Positive: 9 %

Simple and best practice solution for Log[5]x^2=log[5]16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to ...
Read more

Positive: 10 %

Simplifying log(5)(x + 2) + -1log(5)(7) = log(5)(49 ... = log(5)(49) Reorder the terms for easier multiplication: 5glo(2 + x) + -1log(5)(7) = log(5)(49) (2 ...
Read more

Positive: 10 %

Solution for Log[5](x)+log[5](x+2)=log[5](8) equation: Simplifying Log[5](x) + log[5](x + 2) = log[5](8) Reorder the terms for easier multiplication: 5goL ...
Read more

Positive: 10 %

Simple and best practice solution for log(3*x)=log(5)+log(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and ...
Read more

Read more

45 %